Assessing the Impact of the Inner Belt: MIT, Highways, and Housing in Cambridge, Massachusetts. (November 2014) - Moss, Hilary; Zhang, Yinan; Anderson, Andy
Between 1948 and 1971, the Massachusetts Department of Public Works released plans to build a freeway through Cambridge. One route would carve up a working-class neighborhood while another would run alongside MIT. First, we assess the impact of the planning process. While no highway was built, housing stock declined and uncertainly complicated urban renewal. Second, we explore MIT's role in this story. Because its campus lay near a proposed route, the university functioned much like any other stakeholder. Yet its economic importance and its involvement with federal defense gave its administrators access to arguments unavailable to local residents or politicians. MIT functioned as both agent and subject, as a private entity at the mercy of federal and state prerogatives and as an influential public force in its own right, whose institutional knowledge, national importance, and civic significance overshadowed city and community prerogatives.